2009
DOI: 10.1016/j.neuron.2009.12.012
|View full text |Cite
|
Sign up to set email alerts
|

LRRTM2 Functions as a Neurexin Ligand in Promoting Excitatory Synapse Formation

Abstract: Recently, leucine-rich repeat transmembrane proteins (LRRTMs) were found to be synaptic cell-adhesion molecules that, when expressed in non-neuronal cells, induce presynaptic differentiation in contacting axons. We now demonstrate that LRRTM2 induces only excitatory synapses, and that it also acts in transfected neurons similar to neuroligin-1. Using affinity chromatography, we identified α- and β-neurexins as LRRTM2 ligands, again rendering LRRTM2 similar to neuroligin-1. However, whereas neuroligins bind neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
368
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 328 publications
(384 citation statements)
references
References 33 publications
(45 reference statements)
9
368
1
Order By: Relevance
“…All four LRRTM family members display synaptogenic activities in these assays, although the induction strength of LRRTM2 is the strongest (de Wit et al, 2009;Ko et al, 2009;Linhoff et al, 2009). LRRTM2 specifically localizes in excitatory synapses, and not in inhibitory synapses (Linhoff et al, 2009).…”
Section: Lrr Synaptic Adhesion Moleculesmentioning
confidence: 91%
See 4 more Smart Citations
“…All four LRRTM family members display synaptogenic activities in these assays, although the induction strength of LRRTM2 is the strongest (de Wit et al, 2009;Ko et al, 2009;Linhoff et al, 2009). LRRTM2 specifically localizes in excitatory synapses, and not in inhibitory synapses (Linhoff et al, 2009).…”
Section: Lrr Synaptic Adhesion Moleculesmentioning
confidence: 91%
“…A systematic bioinformatics study has shown that extracellular LRR domain-containing proteins have greatly expanded in mammals (135 in mouse, 139 in human) compared with worms (29 extracellular LRR proteins) and flies (66 extracellular LRR proteins) (Dolan et al, 2007). The ligands of these extracellular LRR proteins remain largely unknown, although the process of ligand identification has recently accelerated (de Wit et al, 2009;Ko et al, 2009;Siddiqui et al, 2010;Takahashi et al, 2011;Woo et al, 2009). Mounting evidence from invertebrate systems shows that extracellular LRR proteins control key phases of neuron development and neural circuit formation including axon guidance, target-cell recognition, and synapse formation.…”
Section: Leucine-rich Repeats (Lrrs)mentioning
confidence: 99%
See 3 more Smart Citations